Feasibility and Efficacy Estimate of an Emotion-Focused Version of Cognitive Behavior Therapy for Delusions in Comparison to Wait List in a Single-Blinded Randomized-Controlled Pilot Trial. Issue 1 (27th October 2021) - Mehl, Stephanie; Hautmann, Christopher; Nittel, Clara Marie; Rief, Winfried; Kircher, Tilo; Lincoln, Tania Marie
Abstract: Background: Cognitive Behavior Therapy for psychosis (CBTp) effectively reduces positive symptoms, but the effects for delusions are small. Using approaches that focus on improving putative causal factors of delusions (emotion regulation [ER] and negative self-schemata) may be a way to improve CBTp for delusions. Objectives: To pilot an emotion-focused CBTp intervention comprised of cognitive-behavioral and third-wave interventions targeting ER and negative self-schemata (CBT-E) to investigate its feasibility and its potential efficacy. Methods: A single-blind 2-centered randomized wait-list controlled trial was performed. Patients with delusions in the context of a psychotic disorder ( n = 64) were randomized to CBT-E (treatment group [TG]: n = 35) or wait list (WL: n = 29). TG received individual CBT-E in weekly sessions over 6 months, WL received CBT-E after a 6-month waiting time. Assessments were performed at baseline, after 6 months, and after 12 months. Results: Rates of patients who consented and retained in CBT-E suggest acceptable feasibility and high acceptance of CBT-E. Multiple regression analysis in the intent-to-treat sample revealed no significant advantage in favor of the TG in the primary outcome delusions (PSYRATS delusions, PDI), no effect on the mediators (ER, negative self-schemata) and a significant advantage in only one of the 8 secondary outcome variables, namely general psychopathology. Discussion: Although the intervention was feasible and acceptable, its effects on delusions did not hold up with the effects found for "targeted" approaches in previous research and it needs to be improved to produce a stronger effect on the targets ER and self-schemata before proceeding to a large-scale randomized-controlled trial. Clinicaltrials.gov-Identifier: NCT02787122.